The Ligurian Archive of Popular Writing: Origins and development - Caffarena, Fabio (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2022)
The Ligurian Archive of Popular Writing (L’Archivio Ligure della Scrittura Popolare) was founded in 1986 by Antonio Gibelli in the Department of Modern and Contemporary History. Since 2017, it has served as a research and documentation centre in the Department of Education Sciences at the University of Genova. Its mission is the recovery, study and educational use of nineteenth- and twentieth-century written testimonies by ordinary people, in order to analyse the processes of affirmation of subjectivity that emerge in the writings of migrants, soldiers, workers, women and children.